Targeting DNA repair to enhance the efficacy of sorafenib in hepatocellular carcinoma. Issue 10 (22nd October 2022) - Samadaei, Mahzeiar; Senfter, Daniel; Madlener, Sibylle; Uranowska, Karolina; Hafner, Christine; Trauner, Michael; Rohr‐Udilova, Nataliya; Pinter, Matthias
Abstract: The multityrosine kinase inhibitor sorafenib remains an important systemic treatment option for hepatocellular carcinoma (HCC). Signaling pathways, which are targeted by sorafenib, are involved in checkpoint and DNA repair response, RAD51 being a candidate protein. Here, we aim to evaluate the effect of the human RAD51 inhibitor B02 in combination with sorafenib in human HCC cells. Impact of RAD51 expression on HCC patient survival was evaluated by an in silico approach using Human Protein Atlas dataset. Cell viability of HUH7, AKH12, AKH13, and 3P was assessed by neutral red assay. To measure the cytotoxicity, we quantified loss of membrane integrity by lactate dehydrogenase release. We also employed colony formation assay and hanging drop method to assess clonogenic and invasive ability of HCC cell lines upon sorafenib and B02 treatment. Cell cycle distribution and characterization of apoptosis was evaluated by flow cytometry. In silico approach revealed that HCC patients with higher expression of RAD51 messenger RNA had a significantly shorter overall survival. The RAD51 inhibitor B02 alone and in combination with sorafenib significantly reduced viability, colony formation ability, and invasion capacity of HCC cells. Cell cycle analysis revealed that the combination of both agents reduces the proportion of cells in the G2/M phase while leading to an accumulating in the subG1 phase. The RAD51 inhibitor B02 seems to be a promising agent for HCC treatment and enhances the antitumor effects of sorafenib in vitro.